Technology application competencies for K-12 teachers - Chen, Irene; Thielemann, Jane.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book is designed to strengthen understanding of the critical information in the framework for technology application competencies for K-12 teachers"--Provided by publisher.
1. Technology operation and concepts for teachers -- 2. Teacher productivity and professional practices -- 3. Using technology for learning, teaching, and designing the curriculum -- 4. The principles and applications of digital design -- 5. Desktop publishing for schools -- 6. Creating multimedia for special audiences -- 7. School multimedia design teams and projects -- 8. Video and sound in education -- 9. Design, produce, and distribute educational multimedia products -- 10. Administration of educational web sites -- 11. Web design tools for educators -- 12. Web communications and interaction for teaching and learning.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 27, 2010).
Keywords: Educational technology -- Study and teaching; Information technology -- Study and teaching; Teachers -- Training of; Teachers -- In-service training; Electronic books